Strategi Inovasi Industri Kecil Suku Cadang di Kota Padang - Dina Rahmayanti; Widya Marcelena (The Industrial Engineering Department of Engineering Faculty at Universitas Andalas, 2012)
Small and medium enterprises in Indonesia gave big contributions to create job opportunities for community and increased Gross Domestic Product. Unfortunately, the current SMEs did not get any respect from the government. This is evidenced by many problems that happened with SMEs in Indonesia. Agency Statistic Center conducted survey in 2009 and 2010 and identified causes of the problems are availability of raw materials, financial problem, marketing, fuel or energy, transportation, skills, payment and many others. Formulation of the problems is how to design indicators of innovation that can be used to make policy strategies to solve the problems. The objective of research is to recommend some innovation indicators for spare part in Padang and use the indicators to make innovation policies. Method to determine the ability innovation of spare parts industries is Quality Function Deployment (QFD). The first stage is identify consumer needs. Consumer needs obtained from literatures and interviewed of stakeholders. Then, calculated based on customer importance ratings to obtain critical and non critical indicators. Indicators will be presented into the House of Quality (HOQ). The results of HOQ are determined some strategies by using SWOT analysis. This research result obtained 25 innovation indicators of technology that is divided into three aspects such as technology aspects, design and product quality aspects. Strategy formulation from SWOT analysis result some strategies with 4 categories and among of them are SO strategy (4 strategies), WO strategy (5 strategies), ST strategy (4 strategies), and WT strategy (3 strategies). Besides that, strategy architecture will present strategy implementation for 10 years and completed with some people that have participation to make this strategy implementation successful.